Reducing of gas emissions from the production of calcinated soda ash - Moiseev, V.; Manoilo, Е.; Hrubnik, A.; Liaposhchenko, А.; Khukhryanskiy, О. (Lviv Polytechnic Publishing House, 2018)
Reducing the negative impact on the environment of the production of soda ash is achieved by reducing the formation of gas and dust emissions, as well as their deeper cleaning. The problem of cleaning gas emissions from the production of soda ash is solved by using hollow vortex devices. The advantages of multi-stage vortex-type apparatuses for cleaning large volumes of industrial gas emissions are noted.
Keywords: industrial gas emissions; vortex apparatus; cleaning processes; ammonia; soda ash dust